2015
DOI: 10.1021/acs.jpcb.5b08643
|View full text |Cite
|
Sign up to set email alerts
|

Cosolvent Effects on Solute–Solvent Hydrogen-Bond Dynamics: Ultrafast 2D IR Investigations

Abstract: Cosolvents strongly influence the solute-solvent interactions of biomolecules in aqueous environments and have profound effects on the stability and activity of several proteins and enzymes. Experimental studies have previously reported on the hydrogen-bond dynamics of water molecules in the presence of a cosolvent, but understanding the effects from a solute's perspective could provide greater insight into protein stability. Because carbonyl groups are abundant in biomolecules, the current study used 2D IR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 74 publications
4
42
0
Order By: Relevance
“…This observation is consistent with studies on similar alkyl acetates where the solvents exhibit altered conformations of the terminal methyl group, resulting in differences in the E/Z-rotamer populations, 7779 or the presence of different H-bonding configurations as observed by MD simulations and 2D IR. 8082 Consistent with multiple H-bonding configurations, post-processing of MD trajectories by Pazos et al . showed that the fields and frequencies of these 1- and 2-H-bonding configurations fall on the same field-frequency calibration line as other non-H-bonding solvents, consistent with a linear Stark effect.…”
Section: Resultsmentioning
confidence: 97%
“…This observation is consistent with studies on similar alkyl acetates where the solvents exhibit altered conformations of the terminal methyl group, resulting in differences in the E/Z-rotamer populations, 7779 or the presence of different H-bonding configurations as observed by MD simulations and 2D IR. 8082 Consistent with multiple H-bonding configurations, post-processing of MD trajectories by Pazos et al . showed that the fields and frequencies of these 1- and 2-H-bonding configurations fall on the same field-frequency calibration line as other non-H-bonding solvents, consistent with a linear Stark effect.…”
Section: Resultsmentioning
confidence: 97%
“…The slowing of dynamics identified in heterogeneous micelles indicates that there is a greater amount of water trapped in the surfactant-water interfacial region of these systems. Water molecules penetrating deeper into the surfactant region have restricted access to the collective hydrogen-bond networks that facilitate HB switching in bulk water. Previous work has shown that cosolvents slow HB fluctuations by preventing the instantaneous replacement of one HB for another . Therefore, as water penetration increases, a greater proportion of water molecules enter the crowded surfactant layer, which then lengthens the average HB fluctuation dynamics, as experimentally observed from the 2D IR CLS analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Using the peak positions and anharmonic shift as determined by the 2D IR spectroscopic measurements and estimated T 1 population relaxation times of 1175, 2500, and 840 fs for acetophenone, methyl benzoate, and ethyl thioacetate, respectively, the time-dependent response functions for each of the rephasing and nonrephasing pathways were calculated and used to generate the simulated 2D IR spectra. The vibrational lifetimes ( T 2 ) were in the generally observed range for other simple carbonyl compounds (0.8–5.2 ps ), though this has been tested predominately with amides. The relative intensities of the overtones were scaled in order to more closely match the experimental fits.…”
Section: Methodsmentioning
confidence: 97%